Fair long-term care insurance - Marie-Louise Leroux; Pierre Pestieau; Grégory Ponthiere (Center for Economic Studies and ifo Institute (CESifo), 2019)
The study of optimal long-term care (LTC) social insurance is generally carried out under the utilitarian social criterion, which penalizes individuals who have a lower capacity to convert resources into well-being, such as dependent elderly individuals or prematurely dead individuals. This paper revisits the design of optimal LTC insurance while adopting the ex post egalitarian social criterion, which gives priority to the worst-off in realized terms (i.e. once the state of nature has been revealed). Using a lifecycle model with risk about the duration of life and risk about old-age dependence, it is shown that the optimal LTC social insurance is quite sensitive to the postulated social criterion. The optimal second-best social insurance under the ex post egalitarian criterion involves, in comparison to utilitarianism, higher LTC benefits, lower pension benefits, a higher tax rate on savings, as well as a lower tax rate on labor earnings.
Keywords: J14; I31; H55; 330; long-term care; social insurance; fairness; mortality; compensation; egalitarianism